WITHDRAWAL FROM THE EU – CONSEQUENCES UNDER EU AND INTERNATIONAL LAW - Lukić Radović, Maja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Article 50 TEU, as the sole legal mechanism for withdrawal provided by EU law, affords substantial flexibility to the withdrawal process overall, and to the scope of a possible withdrawal agreement in particular. Considering the unfolding of Brexit thus far, it appears that the flexibility of Art. 50 TEU has withstood the test of practice and proven to be wisely devised. On the other hand, the ongoing deliberately undertaken steps of the UK Government to breach the Withdrawal Agreement and, consequently, EU law, show that the binding effect of EU law is not a legal phenomenon per se, but rather a direct consequence of the political and value-based significance of the EU for its Member States and their citizens. The agreed detailed regulation of rights of individual persons – EU nationals residing, working or studying in the UK and vice versa – in the EU – UK Withdrawal Agreement, despite failures to reach agreement in relation to numerous other issues, shows the strength of the phenomenon of acquired personal rights. Brexit has confirmed in practice that there is still no supranational EU citizenship, independent and different from Member State citizenship. The peculiar and complex institutional setup of the EU causes significant issues in respect of the relations of the withdrawing state with the EU and its remaining Member States, third states and international organizations. The fate of international obligations in relation to third parties, acquired prior to withdrawal by the EU, as well as by the withdrawing state together with the EU, by virtue of mixed agreements, remains unclear and thus creates great uncertainty. Numerous difficulties, disputes, costs and uncertainties created by Brexit seem to confirm the view that the true essence of the EU lies in a political and value-based union which aspires to an even stronger unity than the one that exists at present. A withdrawal from such a union is a phenomenon that is difficult to imagine and regulate.